A method for preparing a high-whiteness thin-edge ceramic basin

By accurately controlling the particle size of ceramic raw materials and adopting vacuum pressurization molding technology, the whiteness and strength of the ceramic basin are improved, and the problems of large thickness and low whiteness of the ceramic basin wall are solved, and the preparation of high-whiteness and thin-edged ceramic basin is realized. , improves the artistic sense and performance of the product.

CN116924775BActive Publication Date: 2024-12-13XIAMEN JIAYU INTELLIGENT SANITARY WARE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310608983.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-29
Publication Date
2024-12-13
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

The existing ceramic basin walls have large thickness, low whiteness, lack artistic sense, and have a sense of distortion.

Method used

By accurately controlling the particle size distribution of raw material particles, vacuum and pressurized molding technology are used, combined with potassium feldspar, quartz powder, alumina and other materials, the density and whiteness of the ceramic pot are improved, and the wall thickness is reduced from 9mm to 5mm. At the same time, it improves strength and wear resistance.

Benefits of technology

The whiteness value of the ceramic basin is increased to above 70°, the wall thickness is reduced, and the strength remains unchanged. The ceramic basin becomes light and beautiful, increasing the sense of art and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005103055890000041
    Figure GDA0005103055890000041
  • Figure GDA0005103055890000051
    Figure GDA0005103055890000051
Patent Text Reader

Abstract

The present application relates to the field of ceramic technology, and in particular to a method for preparing a high-whiteness thin-edge ceramic basin. The method comprises the following steps: slurry preparation: the aging time is 7-10 days, slurry injection molding: the slurry is slurried in a mold for slurry injection molding, and then the slurry is fed, consolidated, vacuumed, pressed, demolded, dried and fired to obtain a high-whiteness thin-edge ceramic basin with a whiteness greater than 70°, a thickness of 5mm, and a strength greater than 75MPa, which is beautiful, elegant and artistic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ceramic technology, and in particular to a method for preparing a high-whiteness thin-edge ceramic basin. Background Art

[0002] Sanitary ceramics are glazed ceramic products used in bathrooms, kitchens, laboratories, etc., including wash basins, water tanks, sinks, bathtubs, soap boxes, and dressing table boards. Currently, most ceramic basins have thick walls, usually more than 9mm, and are relatively heavy overall, with a whiteness value of around 30°. In addition, due to the thick walls, there is a sense of height distortion and no artistic sense. Summary of the invention

[0003] The purpose of this application is to provide a method for preparing a high-whiteness thin-edge ceramic basin in response to the deficiencies of current technology, achieving a high-whiteness thin-edge ceramic basin with a whiteness value of more than 70°, a wall thickness of 5mm, high strength, and an artistic feel.

[0004] To achieve the above objectives, this application provides the following technical solutions:

[0005] A method for preparing a high-whiteness thin-edge ceramic basin comprises the following steps:

[0006] S1 slurry preparation: in terms of mass percentage, the green body comprises the following components: 4-8 parts of potassium feldspar, 4-8 parts of quartz powder, 2-4 parts of calcined talc, 45-55 parts of alumina, and 0.5-1.5 parts of dolomite. The weighed raw materials are loaded into a ball mill, and then an appropriate amount of water is added for wet grinding until the particle size is less than 325 meshes, and then 23-27 parts of white mud, 7-10 parts of black mud, and 3-6 parts of kaolin are added and the mixture is continuously ball-milled until the particle size is less than 10 μm and the proportion is 70-75%, and then the slurry is discharged from the mill, and then the slurry is prepared through screening, iron removal, and aging for standby use, and the aging time is 7-10 days.

[0007] S2 grouting molding: The slurry is slurry-injected into the mold for molding. After slurrying, consolidation, vacuuming, pressure molding, and demoulding, it is dried at 60-70℃ to a moisture content of less than 3% to obtain a high-whiteness thin-edge ceramic basin green body.

[0008] S3 firing: The high-whiteness thin-edge ceramic green body is loaded into the kiln for sintering. The firing process is: heating from room temperature to 400-450°C at a rate of 6-8°C / min and keeping warm for 30 minutes, then heating to 900-950°C at a rate of 8-10°C / min, and finally heating to 1220-1240°C at a rate of 3-5°C / min and keeping warm for 10-20 minutes to obtain a high-whiteness thin-edge ceramic basin.

[0009] By adopting the above technical solution, the density of the ceramic basin is improved through precise control of the particle size distribution of the raw material particles, thereby improving its strength. Potassium feldspar contains potassium and sodium, which acts as a solvent, can shorten the firing time, increase the light transmittance of the ceramic basin, and improve the high temperature resistance, compressive strength and impact resistance. Quartz can improve the wear resistance and surface flatness of the ceramic basin. The role of alumina is as the main component of the ceramic basin, improving the hardness, corrosion resistance and insulation of the ceramic basin. Dolomite improves the brightness of the ceramic basin and reduces the sintering temperature. White mud increases the viscosity of the mud during the preparation process, greatly improving the whiteness value of the ceramic basin. Black mud enhances the toughness and elasticity of the ceramic basin. Kaolin increases the strength and deformation resistance of the body during the preparation process.

[0010] Through long-term aging, the aging time is 7-10 days, and sufficient and efficient fermentation, it is possible to effectively remove residual trace organic matter in the mud, reduce subsequent gas generation, and create the prerequisite for obtaining a high-density ceramic basin.

[0011] Preferably, in the slurrying step S1, the performance parameters of the slurry are: specific gravity is 1.800kg / L-1.900kg / L, fluidity is 100mL glaze slurry flow time is 30-70 seconds.

[0012] Preferably, in the pulping step S1, the screening is controlled to be 325 mesh screening, and the screen residue is less than 1%.

[0013] Preferably, in the slurrying step S2, the vacuum degree of the vacuum extraction is 3000-5000Pa.

[0014] Preferably, in step S2, the pressurizing pressure is 200-300 kgf / cm 2 And maintain the pressure for 1h-2h.

[0015] By adopting the above technical solution, the residual gas in the ceramic basin is extracted by vacuuming to enhance its density. At the same time, through pressure molding, the strength of the thin-edge ceramic basin is greatly improved, and the wall of the ceramic basin is reduced from 9mm to 5mm, but its strength does not change, and its strength value is ≥75MPa.

[0016] Preferably, in the slurrying step S2, the thickness of the high-whiteness thin-edge ceramic basin green body is 5 mm.

[0017] Preferably, in the pulping step S4, the whiteness value of the high-whiteness thin-edge ceramic basin is ≥70°.

[0018] Preferably, in the pulping step S4, the water absorption rate of the high whiteness thin-edge ceramic basin is less than 0.5%

[0019] By adopting the above technical solution, the whiteness of the ceramic basin is increased from the conventional 30° to more than 70°, which improves the overall brightness and aesthetics of the ceramic basin, making the product thin and light, beautiful and atmospheric with high whiteness and elegance, increasing the artistic sense of the product and giving the ceramic basin artistic value.

[0020] In summary, the beneficial technical effects of this application are:

[0021] 1. This application improves the density of ceramic basins by precisely controlling the particle size distribution of raw material particles.

[0022] 2. By adopting vacuum extraction and pressure molding, the strength of the thin-edge ceramic basin is greatly improved, and the wall of the ceramic basin is reduced from 9mm to 5mm, but its strength does not change, and its strength value is ≥75MPa.

[0023] 3. The whiteness of the ceramic basin is increased from the conventional 30° to more than 70°, which improves the overall brightness and beauty of the ceramic basin, making the product thin and light, beautiful and atmospheric with high whiteness and elegance, increasing the artistic sense of the product and giving the ceramic basin artistic value. DETAILED DESCRIPTION

[0024] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0025] Example 1

[0026] A method for preparing a high-whiteness thin-edge ceramic basin comprises the following steps:

[0027] S1 slurry preparation: According to mass percentage, the green body includes the following components: 4kg potassium feldspar, 4kg quartz powder, 2kg burned talc, 45kg alumina, and 0.5kg dolomite. The weighed raw materials are loaded into a ball mill, and then appropriate amount of water is added for wet grinding until the particle size is less than 325 mesh. Then 23kg white mud, 7kg black mud, and 3kg kaolin are added and the mixture is continued to be ball milled until the particle size is less than 10μm, accounting for 70%. Then the slurry is discharged from the mill, and then it is sieved, iron removed, and aged to make mud for use. The sieving is controlled to be 325 mesh, the sieve residue is less than 1%, and the aging time is 7 days. The performance parameters of the mud are: specific gravity is 1.800kg / L, fluidity is 100mL glaze slurry flow time is 70 seconds.

[0028] S2 grouting molding: The slurry is slurry-casted in the model, and after slurrying, consolidation, vacuuming, pressurizing, and demoulding, it is dried at 60°C to a moisture content of 3% to obtain a high-whiteness thin-edge ceramic basin green body. The vacuum degree of vacuuming is 3000Pa, and the pressurizing process conditions are: pressure of 200kgf / cm 2 And maintain the pressure for 2h.

[0029] S3 firing: The high-whiteness thin-edge ceramic green body is loaded into the kiln for sintering. The firing process is: heating from room temperature to 400°C at a rate of 6°C / min and keeping warm for 30 minutes, then heating to 900°C at a rate of 8°C / min, and finally heating to 1220°C at a rate of 3°C / min and keeping warm for 10 minutes to obtain a high-whiteness thin-edge ceramic basin with a wall thickness of 5mm.

[0030] Example 2

[0031] A method for preparing a high-whiteness thin-edge ceramic basin comprises the following steps:

[0032] S1 slurry preparation: According to mass percentage, the green body includes the following components: 8kg potassium feldspar, 8kg quartz powder, 4kg burned talc, 55kg alumina, and 1.5kg dolomite. The weighed raw materials are loaded into a ball mill, and then appropriate amount of water is added for wet grinding until the particle size is less than 325 mesh. Then 27kg white mud, 10kg black mud, and 6kg kaolin are added, and the ball milling mixture is continued until the particle size is less than 10μm, accounting for 75%. Then the slurry is discharged from the mill, and then it is sieved, iron removed, and aged to make mud for use. The sieving is controlled to be 325 mesh, the sieve residue is less than 1%, and the aging time is 10 days. The performance parameters of the mud are: specific gravity is 1.900kg / L, fluidity is 100mL glaze slurry flow time is 30 seconds.

[0033] S2 grouting molding: The slurry is slurry-casted in the model, and after slurrying, consolidation, vacuuming, pressurizing, and demoulding, it is dried at 60-70℃ to a moisture content of 2.1% to obtain a high-whiteness thin-edge ceramic basin green body. The vacuum degree of vacuuming is 5000Pa, and the pressurizing process conditions are: pressure 300kgf / cm 2 And maintain the pressure for 1h.

[0034] S3 Firing: The high whiteness thin edge ceramic green body is loaded into the kiln for sintering. The firing process is: heating from room temperature to 450℃ at a rate of 8℃ / min and keeping warm for 30min, then heating to 950℃ at a rate of 10℃ / min, and finally heating to 1240℃ at a rate of 5℃ / min and keeping warm for 20min to obtain a high whiteness thin edge ceramic basin. Its wall thickness is 5mm.

[0035] Example 3

[0036] A method for preparing a high-whiteness thin-edge ceramic basin comprises the following steps:

[0037] S1 slurry preparation: According to mass percentage, the green body includes the following components: 6kg potassium feldspar, 6kg quartz powder, 3kg burned talc, 50kg alumina, and 1.0kg dolomite. The weighed raw materials are loaded into a ball mill, and then appropriate amount of water is added for wet grinding until the particle size is less than 325 mesh. Then 26kg white mud, 8kg black mud, and 5kg kaolin are added and the mixture is continued to be ball milled until the particle size is less than 10μm, accounting for 73%. Then the slurry is discharged from the mill, and then it is sieved, iron removed, and aged to make mud for use. The sieving is controlled to be 325 mesh, the sieve residue is less than 1%, and the aging time is 9 days. The performance parameters of the mud are: specific gravity is 1.850kg / L, fluidity is 100mL glaze slurry flow time is 50 seconds.

[0038] S2 grouting molding: The slurry is slurry-casted in the model, and after slurrying, consolidation, vacuuming, pressurizing, and demoulding, it is dried at 65°C to a moisture content of 1.5% to obtain a high-whiteness thin-edge ceramic basin green body. The vacuum degree of vacuuming is 4000Pa, and the pressurizing process conditions are: pressure 250kgf / cm 2 And maintain the pressure for 1.5h.

[0039] S3 Firing: The high whiteness thin edge ceramic green body is loaded into the kiln for sintering. The firing process is: the temperature is raised from room temperature to 430℃ at a rate of 7℃ / min and kept at this temperature for 30min, then raised to 930℃ at a rate of 9℃ / min, and finally raised to 1230℃ at a rate of 4℃ / min and kept at this temperature for 15min, thus obtaining a high whiteness thin edge ceramic basin. Its wall thickness is 5mm.

[0040] Comparative Example 1

[0041] Same as Example 3, except that the aging time is 3 days.

[0042] Comparative Example 2

[0043] The same as Example 3, except that the amount of white mud added is 10 kg.

[0044] Comparative Example 3

[0045] The same as Example 3, except that vacuum and pressure molding are not used.

[0046] Performance Testing

[0047] The high whiteness thin-edge ceramic basins in Examples 1-3 and Comparative Examples 1-3 were sampled and tested, and the test results are shown in Table 1.

[0048] Strength: Determined in accordance with GB / T 8488-2008 “Test method for compressive strength of ceramic products”.

[0049] Whiteness value: Whiteness value was measured by whiteness meter, with GSB A67002-86 ceramic standard white plate as the standard plate.

[0050] Water absorption rate: Soak the ceramic sample completely in water, take it out after 10 hours, wipe the surface moisture with a dry cloth, and then weigh it. Then put the sample in an oven to dry until the weight no longer changes, weigh it, and calculate the water absorption rate. Water absorption rate = (weight after drying - dry weight) / dry weight × 100%.

[0051] Table 1

[0052]

[0053]

[0054] As can be seen from Table 1, the high-whiteness thin-edge ceramic basin of the present application has a whiteness value greater than 70°, a water absorption rate less than 0.5%, and a strength greater than 76 MPa.

[0055] It can be seen from Comparative Example 1 that when the aging time is 3 days, the water absorption rate of the white thin-edge ceramic basin increases from 0.3% to 10.2%, and the strength value decreases from 79MPa to 58MPa, indicating that when the aging time is insufficient, residual organic matter will release gas during subsequent sintering, resulting in a decrease in the density of the ceramic basin, a decrease in strength, and a significant increase in water absorption rate.

[0056] From Comparative Example 2, it can be seen that as the amount of white mud added decreases, the whiteness value of the thin-edged ceramic basin drops from 76° to 35°, and the whiteness value is greatly reduced.

[0057] It can be seen from Comparative Example 3 that without adopting vacuum and pressure molding, the water absorption rate of the white thin-edge ceramic basin increases from 0.3% to 13.8%, and the strength value decreases from 79MPa to 53MPa, indicating that when vacuum and pressure molding measures are not adopted, the density of the obtained white thin-edge ceramic basin decreases, the strength decreases, and the water absorption rate increases significantly.

[0058] The above embodiments are only used to explain the technical solutions of the present invention rather than to limit the same. Although the above embodiments specifically describe the present invention, relevant technical personnel should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a high-whiteness thin-edge ceramic basin, characterized in that: The following steps are involved: S1 slurry preparation: The raw materials of the ceramic basin include the following components: 6kg potassium feldspar, 6kg quartz powder, 3kg calcined talc, 50kg alumina, and 1.0kg dolomite. The weighed raw materials are loaded into a ball mill, and then an appropriate amount of water is added to wet grind until the particle size is less than 325 mesh. Then 26kg white mud, 8kg black mud, and 5kg kaolin are added to continue ball milling and mixing until the particle size is less than 10μm and the proportion is 73%. Then, the slurry is discharged from the mill, and then sieved, iron removed, and aged to make mud for use. The sieving is controlled to be 325 mesh, the sieve residue is less than 1%, and the aging time is 9 days. The performance parameters of the mud are: specific gravity is 1.850kg / L, fluidity is 100mL glaze slurry flow time is 50 seconds; S2 grouting molding: The slurry is slurry-casted in the model, and after slurrying, consolidation, vacuuming, pressurizing, demoulding, drying at 65℃ to a moisture content of 1.5%, a high-whiteness thin-edge ceramic basin green body is obtained. The vacuum degree of vacuuming is 4000Pa, and the pressurizing process conditions are: pressure 250kgf / cm 2 And maintain the pressure for 1.5h; S3 sintering: the high whiteness thin edge ceramic green body is loaded into the kiln for sintering, and the sintering process is: the temperature is increased from room temperature to 430°C at a heating rate of 7°C / min and kept at this temperature for 30min, then increased to 930°C at a heating rate of 9°C / min, and finally increased to 1230°C at a heating rate of 4°C / min and kept at this temperature for 15min, to obtain a high whiteness thin edge ceramic basin with a wall thickness of 5mm; The whiteness value of the high whiteness thin-edge ceramic basin is 76°; The water absorption rate of the high whiteness thin-edge ceramic basin is 0.3%; The strength of the high-whiteness thin-edge ceramic basin is 79 MPa.